STRATEGI KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND IMAGE PADA MEDIA SOSIAL TWITTER @PekanbaruCo - Mega Febriani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Social media twitter is a gathering place for those people who want to shareinformation and a place to make new friends and interact online. Therefore, todaymany social media twitter accounts are present using the brand image as businessaccount because success of the twitter to promote products and services. Amidst themany other competitors that carries the same brand image, @PekanbaruCo managein building a brand image as a business accounts evidenced by an increase infollowers and clients. The background of this study aims to determine how marketingcommunication strategies social media twitter @PekanbaruCo in building brandimage and what supporting and inhibiting factors of marketing communicationstrategyto build brand image a social media twitter @PekanbaruCo.This study will be held in CV. Mitra Promo Andalan at Jalan Sekuntum 2No. 2 Delima, Tampan, Pekanbaru. The study will use a purposive samplingtechnique (purposive sampling). The Informans in this study are 7 peoples, thatconsist of 1 leader of CV.Mitra Promo Andalan, 1 founder of @PekanbaruCo,2clients, and 3 followers of sosial media twitter @PekanbaruCo.The result showed the marketing communication strategy that do in sosialmedia twitter @PekanbaruCo to build brand image through advertising, salespromotion, personal selling, publicity, direct marketing. Good relationship withclients and good networking with the other business accounts as supporting factor.The inhibiting factors of marketing communication strategy in building brand imageare lack of education about social media marketing, lack of human resource, andlimited budget.Keywords: marketing communication strategy, social media twitter, brand image